The Moral Foundation of Criminal Defences and the Limits of Constitutional Law - Fehr, Colton (McGill Law Journal / Revue de droit de McGill, 2023)
The Supreme Court of Canada’s decision in R v Khill provided a novel moral framework for self-defence. Whereas self-defence was previously categorized as a justification, the Court now maintains that it constitutes an excuse in some cases. In other cases, the Court suggests self-defence sits between justification and excuse, captured by a principle I elsewhere call “moral permissibility”. The Court’s choice to adopt a more robust relationship between the moral principles underlying justification/excuse and self-defence is principled. However, the basis for that conclusion—the application of moral philosophy to the law of criminal defences—applies with equal force to the law of duress and necessity. Unfortunately, the statutory duress defence and section 8(3) of the Criminal Code limit the juristic scope of those defences. Although these restrictions may be challenged under section 7 of the Charter, this challenge will likely fail as defendants need not be denied a defence. Instead, they will be denied a proper moral assessment of their actions. To instill greater coherency into the law, it is prudent to repeal the statutory duress defence. This approach would allow courts to utilize the broad wording of the new “defence of person” provision to develop the law of self-defence, necessity, and duress in line with the moral philosophy underlying these defences. Constitutionalizing the principles underlying criminal defences can nevertheless serve two broader purposes: mitigating the tendency of courts and counsel to unduly rely upon other less transparent (jury nullification) or heavy-handed (judicial review) legal devices to avoid conviction.